Exploiting reliable features of the ocean channel response - Porter, M. B. (2014)
Modelling sound propagation in shallow water is notoriously difficult. The main difficulties are, of course, ocean variability characteristic of coastal waters and the typpicaly downward refracting profiles that make the acoustic field extremely sensitive to the bottom characteristics. Meanwhile accurate prediction of transimission loss curves at a single frequency requires that the relative phase of each surface and bottom echo is predicted with precision.